Month-to-month variability of the melting layer boundaries - Khamis, Nor Hisham; Sharif, Omer Abdel Razag; Hanzaz, Zakaria; Baharom, Ameruddin (2008)
The Bright-band is the typical enhancement in radar reflectivity during the melting process, which is still not completely determined. The seasonal variation over the year can give the characteristics that are valuable for designing and planning of a satellite link. The Malaysian Meteorological radar data, from Kluang Radar Station (Johor), is used to trace the signature of the melting layer during stratiform precipitations events. The trends of the boundaries of the melting layer were studied by considering data extended to cover a six-month period (January -June 1998). It was observed that the boundaries and the thickness of the melting layer are found to be seasonally dependent.